Development of entrepreneur structures in the field of renewable energy through improving public-private partnership mechanisms - Tiesheva, L.; Shteimiller, I. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The development of decarbonization technologies and their deployment through the introduction and spread of innovative technology, which is required owing to climate change, is a significant precursor in the renewable energy sector. When it comes to creating technology to lower CO2 emissions and putting decarbonization plans into action, startups are crucial. The study, which was based on the integrative review methodology and system approach, showed that ongoing technological innovation, which permits the application of contemporary technologies to create effective and efficient solutions to the current challenges in the energy market, is what drives start-ups’ growth momentum. Startups actively support decentralized energy models by investigating the application of technologies like local energy generation systems and microgrids. The results demonstrate that in order to maximize efficiency and profitability throughout the shift to renewable energy, new business models and technological innovation are needed, making these technologies scalable and financially feasible through integrated methods. The issue of private sector’ motivation towards participation in public-private partnership is explored in the context of development of business structures and optimal matching of public and private partners for renewable energy projects. The findings contribute to enhancing the possibilities of better planning and designing policies in public-private partnership within renewable energy sector, and, moreover, can be used by sector entrepreneurs when considering decisions on participation in public-private partnership. Moreover, the effective implementation of renewable energy projects largely depends on the quality of the institutional environment and the stability of regulatory policies. In this context, public–private partnerships serve as an instrument for reducing investment risks and stimulating the innovative activity of startups. The synthesis of scientific sources indicates that the combination of public support with the entrepreneurial flexibility of the private sector creates favorable conditions for accelerating decarbonization processes. Thus, the development of startups within public–private partnerships contributes to the formation of a sustainable, innovation-driven, and competitive renewable energy sector.